Beyond Philosophy Nietzsche, Foucault, Anzaldúa - Tuana, Nancy (Indiana University Press, 2020)
Questions of whether anything exceeds reasonable sense and meaning have persisted throughout the history of philosophy. These questions have even continued in postmodern thought as well as in liberatory philosophies in which many kinds of events and lineages are experienced and seen as beyond philosophy. In this cowritten text, distinguished philosophers Nancy Tuana and Charles Scott pay particular attention to lineages and their dynamism as they develop the idea of things beyond philosophy, beyond norms. This is not a history of philosophy or a critical study of a particular philosopher but a way to engage experience around dimensions of events that are beyond measuring, counting, meaning, and value. These attunements, they assert, are vitally important for the ways people orient themselves in the world and comport themselves in it. Tuana and Scott build on the alternatives to normative ethics that they find in the work of Nietzsche, Foucault, and Anzaldúa. They urge attunement to the world as a way to speak about what is impossible to give voice to, to live in the spaces between speech and the unspeakable, and to conceptualize and articulate the boundaries of rational sensibility.